Endovascular Embolization of a Lateral Sacral Fistula: 2‐Dimensional Operative Video. Issue 3 (September 2020) - Rahme, Rudy J.; Abi‐Aad, Karl R.; Almekkawi, Ahmad Kareem; Patra, Devi P.; Bendok, Bernard R.
Abstract : N/A: Spinal dural arteriovenous fistulas are the most common vascular malformations of the spine. They are localized in the sacral spine in 5% to 14% of the cases. They can be fed by the median or the lateral sacral arteries. These lesions present with nonspecific symptoms such as radiculopathy and/or myelopathy, which often leads to a delay in diagnosis. In this video, we present the case of a 65‐yr‐old gentleman with a lateral sacral dural arteriovenous fistula. The patient was referred to our institution after the outside facility workup was nondiagnostic. He presented with spastic paraparesis and bilateral radiculopathy. After patient informed consent was obtained, we performed a spinal diagnostic angiogram with catheterization and angiography of the internal iliac artery, which revealed the fistula. Onyx (Medtronic, Dublin, Ireland) embolization was performed, which led to a complete occlusion of the fistula. The patient had complete neurological recovery, and at 2‐yr follow‐up, imaging remained negative for a fistula. In this video, we discuss the nuances and key points related to the epidemiology, diagnosis, and treatment of lateral sacral fistulas.1‐3